Me and My Monsters: A multispecies study on schistosomiasis in Sub-Saharan Africa - Parrott, Charne (School of African and GenderStuds, Anth and Ling, 2024)
For such microscopic creatures, schistosomes have become monstrous in scale and impact across the World's tropics, and particularly in Sub-Saharan Africa. Schistosomes are parasitic blood-fluke worms and their disease, schistosomiasis, is an ancient disease that has evolved with humans for centuries and it is through its connections to humans that it has thrived. This dissertation outlines the actor-network surrounding schistosomiasis through a multispecies lens. Tsing et al.'s (2017) ‘monsters' is utilised to argue that schistosomiasis is a man-made disease, and our influence of nature only exacerbates the situation. Secondly, the purpose of this dissertation is to bring illness narratives to expand our understanding of what it is like to live with these parasites. Lastly, it analyses the social, economic and political structures that made and sustains schistosomiasis as the second most important neglected tropical disease in the world (Adekiya et al., 2020). This is a deadly, slow killing disease that affects millions of people around the world, yet it and the people most at risk of contracting it are severely neglected. It is only through an understanding of the interconnectedness of the actors in this network and acknowledging the social, economic and political processes that hinder, or even aggravate, the control of schistosomiasis that a holistic, successful intervention can be designed.